Pembelajaran Pendidikan Agama Islam Masa Pandemi Covid-19 - Santoso, Subhan Adi (Jurnal Pendidikan Islam, 2022)
The background of this research is starting from the current problems with the COVID-19 virus outbreak which has made almost all aspects of being locked down, including education which requires learning from home or studying using an online system (in the network), from learning in the network. Researchers want to see and conduct a study on the role of parents in assisting children in the PAI learning process in the Covid-19 era. This study aims to find out how the role of parents in assisting the fiqh learning process in the Covid-19 era at MTs Muhammadiyah 06 Banyutengah. The approach used is a qualitative approach which is carried out by field observations. Data collection techniques are by conducting field observations, interviews and documentation from schools. Data analysis techniques used as learning materials are data reduction, data presentation and conclusion drawing.The results of this study are the role of parents in assisting children in the learning process on fiqh subjects at MTS Muhammadiyah 06 Banyutengah. The obstacles experienced were due to 1) signals 2) electronics 3) lack of facilities 4) costs for purchasing data packages. Learning within the network itself is related to online learning, MTS Muhammadiyah 06 Banyutengah uses media, namely WhatsApp as a learning medium and as a learning evaluation. The success of the implementation of online learning for this year has reached 70% because there are still many obstacles experienced by students when doing online learning, even though the school has provided facilities to teachers which is one form of support for online learning so that it is optimal in providing online learning.